KONSEPSI FEMINISME DAN KESETARAAN GENDER DALAM PERSPEKTIF HUKUM ISLAM: ANTARA FENOMENA DAN REALITA - Sulistiyaningsih, Nur (EGALITA, 2024)
This research examines the conception of feminism and gender equality from an Islamic legal perspective. There are inherent traits in men and women that are constructed socially and culturally, but in reality, women are often placed as optional after men because of patriarchal culture. This research will soon examine the phenomenon and reality of feminism and gender equality in society from an Islamic legal perspective. This research method uses descriptive analysis by collecting primary and supporting data for analysis based on Islamic Law. The research results of this paper confirm that both progressive and traditional thinkers agree that in Islamic law, there is no favoritism towards one group. Men and women have the same position, even though the phenomenon and reality of society are still affected by patriarchal culture and gender discrimination. Gender equality and gender justice are essential for achieving equality between all genders. Gender justice focuses on the fair distribution of opportunities according to the needs of each individual, while gender equality focuses on equal rights and opportunities for all, regardless of gender. Islam teaches the importance of balance and justice and rejects all forms of injustice, emphasizing that both genders have complementary roles in the family and society.